PULL AND BENDING FORCE CARBON FIBER COMPOSITE - Moh Ardi Cahyono; Laura Laksamana (Vortex, 2020)
Based on the test data, it can be seen that the average stress value on the carbon fiber composite with the fiber direction of 0 ° -30 ° -60 ° has the highest tensile stress value in the TA 2 specimen, namely 121.439 MPa, the highest strain value in the TA 1 specimen is 0.031, the value The highest modulus of elasticity in the TA 3 specimen is 438,460 MPa, while for the fiber direction 0 ° -45 ° -90 ° the highest tensile stress value in the TB 3 specimen is 670.691 MPa, the highest strain value in the TB 3 specimen is 0.096, the highest elasticity modulus value in the specimen TB1 is 1076,993 MPa.